Transient antibody targeting of CD45RC induces transplant tolerance and potent antigen-specific regulatory T cells - Picarda, Elodie (JCI Insight, 2017)
Rat and human CD4(+) and CD8(+) Tregs expressing low levels of CD45RC have strong immunoregulatory properties. We describe here that human CD45 isoforms are nonredundant and identify distinct subsets of cells. We show that CD45RC is not expressed by CD4(+) and CD8(+) Foxp3(+) Tregs, while CD45RA/RB/RO are. Transient administration of a monoclonal antibody (mAb) targeting CD45RC in a rat cardiac allotransplantation model induced transplant tolerance associated with inhibition of allogeneic humoral responses but maintained primary and memory responses against cognate antigens. Anti-CD45RC mAb induced rapid death of CD45RC(high) T cells through intrinsic cell signaling but preserved and potentiated CD4(+) and CD8(+) CD45RC(low/–) Tregs, which are able to adoptively transfer donor-specific tolerance to grafted recipients. Anti-CD45RC treatment results in distinct transcriptional signature of CD4(+) and CD8(+) CD45RC(low/–) Tregs. Finally, we demonstrate that anti-human CD45RC treatment inhibited graft-versus-host disease (GVHD) in immune-humanized NSG mice. Thus, short-term anti-CD45RC is a potent therapeutic candidate to induce transplantation tolerance in human.